KAJIAN PERLINDUNGAN HUKUM BAGI KORBAN KEKERASAN DALAM RUMAH TANGGA DI WILAYAH HUKUM KEPOLISIAN RESORT KOTA SURAKARTA - SUWANTA, SUWANTA (Dinamika Hukum, 2016)
This thesis discusses on the effort of legal protection on the victim of domestic violence. This research aims at obtaining an understanding on the legal protection on people who become victims of the crime of domestic violence. The role of legal officers in protecting the rights of the victims of domestic violence has been begun since receiving a report on the occurence of the crime of domestic violence from the victim to the investigation time at the court. It starts from the police agency that receives a report/complaint from the victim of domestic violence. Then after receiving the report from the victim of violence, the police investigator examines the victim soon and take a step to give a temporary protection for the victim of domestic violence, that is for period of 7 (seven) days. In giving protection to the victim, the police investigator cooperates with Badan Perlindungan Masyarakat (Bapermas/Agency for Public Protection), Non Government Organization (NGO), Dinas Sosial/Social Agency, the victim's family as well as the Head of Environment/Neighborhood Association. In the effort of giving protection to the victim of domestic violence, the police side that cooperates with the above related agencies places the victim in a â€œSafehouseâ€ or an â€œAlternative Residenceâ€, to protect the victim from the perpetrator's continuation violence. In handling the case of domestic violence, the investigator' main mission is to mediate/reconcile the victim and the perpetrator in order to live in harmonic in the domestic affairs. If the mediation is successful, the case is stopped through the report withdrawal by the victim through the making of Letter of Reconciliation. If the mediation process does not produce a result (fail), based on the Victim' Information, Witnesses, the Perpetrator and other evidences, the investigator will give opinion whether the case is suitable to be proposed to the process of lawsuit or not. In the effort of giving legal protection to the victim of domestic violence, several obstacles are found. The obstacles, among others, are caused by the factor of the law itself, the factor of the legal enforcement officers, the factor of infrastructure and facilities, the factor of society, and the factor of culture. Keywords: Domestic Violence, Victim, Legal Protection.